Legal terms of use and public genealogy websites. Issue 1 (7th November 2020) - Contreras, Jorge L; Schultz, Kyle; Teerlink, Craig C; Maness, Tim; Meyer, Laurence J; Cannon-Albright, Lisa A
Abstract: Public genealogy websites, to which individuals upload family history, genealogy, and sometimes individual genetic data, have been used in an increasing number of public health, epidemiological, and genetic studies. Yet there is little awareness among researchers of the legal rules that govern the use of these online resources. We analyzed the online Terms of Use (TOU) applicable to 17 popular genealogy websites and found that none of them expressly permit scientific research, while at least 13 contain restrictions that may limit or prohibit scientific research using data obtained from those sites. In order to ensure that researchers who use genealogy and other data from these sites for public health and other scientific research purposes do not inadvertently breach applicable TOUs, we recommend that genealogy website operators consider revising their TOUs to permit this activity.